Bacterial respiration keeps amazing us in the 21st century. (23rd December 2021) - Hards, Kiel; Cook, Gregory; Jeuken, Lars J.C.
Abstract : The last two decades have seen some remarkable discoveries in bacterial bioenergetics. In this article, we highlight how important societal issues such as antimicrobial resistance and sustainable fuel production have led to a renewed focus on the bioenergetics of bacteria, which is only beginning to show us how much we have left to learn. Advances in technology, particularly through biophysics, have further contributed to a rapid progress in our understanding of the respiratory chain complexes in bacteria. Blue-sky research has seamlessly merged with solutions to societal problems and we stand on the precipice of a number of exciting discoveries in this field.